2021
DOI: 10.1021/acs.orglett.1c01137
|View full text |Cite
|
Sign up to set email alerts
|

SOMO–HOMO Conversion in Triplet Carbenes

Abstract: In this study, the SOMO−HOMO conversion has been shown for the first time in triplet carbenes embedded in cycloparaphenylene units. The high-lying HOMO originating from the curved π-conjugated system and the low-lying SOMO−1 originating due to the small carbene angle are the key to endowing this interesting electronic configuration. Furthermore, simple planar triplet carbenes such as fluorenylidene were found to possess SOMO− HOMO energy-converted electronic configurations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Recently, SOMO−HOMOconverted triplet carbenes have been found by this laboratory. 15 The search for molecules that undergo SOMO−HOMO conversion will advance the field of radical chemistry.…”
Section: ■ Introductionmentioning
confidence: 51%
See 1 more Smart Citation
“…Recently, SOMO−HOMOconverted triplet carbenes have been found by this laboratory. 15 The search for molecules that undergo SOMO−HOMO conversion will advance the field of radical chemistry.…”
Section: ■ Introductionmentioning
confidence: 51%
“…Although the reactivity of SOMO–HOMO-converted molecules has attracted considerable attention in radical chemistry, only a limited number of organic molecules have been reported to date. Recently, SOMO–HOMO-converted triplet carbenes have been found by this laboratory . The search for molecules that undergo SOMO–HOMO conversion will advance the field of radical chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…In 2021, SHC in triplet carbenes were reported by Abe, Antol, and their co-workers. [35] The SHC in nC, triplet carbenes embedded in cycloparaphenylene (CPP), and simple triplet diaryl carbenes was confirmed computationally (Figs 14 and 15) at the UB3LYP/6-31G(d) level of theory. CPP is known to have a higher HOMO level with a smaller ring size due to the increase in quinoidal character (Fig.…”
Section: Carbenes and Diradicalsmentioning
confidence: 81%
“…In 2021, Abe, Antol, et al reported another example of this type of molecular design, based on carbene derivatives displaying SHI. 54 Based on theoretical calculations, it was shown that triplet carbenes included in a cycloparaphenylene (CPP) scaffold have SOMO energy levels below the HOMO of the CPP ring (Figure 17). This electronic configuration is found for the ring composed of four phenyl units (25), whereas in larger carbene-CPP derivatives (5 to 10 phenyl units), the HOMO lies energetically in between the two SOMOs.…”
Section: Shi Radicals From Symmetric Dimer Compoundsmentioning
confidence: 99%
“…This SOMO-HOMO inversion (SHI), alternatively referred to as SOMO-HOMO conversion or a quasi-closed-shell configuration, has generated widespread interest, both theoretically and experimentally, to rationalize and understand the consequences of the peculiar electronic structure of this class of open-shell systems. 23,50,[53][54][55][56][57] SHI has been investigated in organic spin-polarized donor systems as a route toward high-spin diradicals, 18,[58][59][60][61][62] and also in the case of luminescent radicals where SHI was associated with a significant increase of photostability. 38 Coote, Corminboeuf et al summarized various theoretical aspects related to the characterization of this phenomenon with molecular examples of SHI in 2015.…”
Section: Introductionmentioning
confidence: 99%